Implementasi Pendidikan Karakter Berdasarkan Nilai Pancasila di Era Globalisasi - Lin Herlina; Dinie Anggraeni Dewi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
Moral educationis one of the important things for the life of the Indonesian nation. Pancasila is used as the basis of the state, Pancasila is also the ideology of the state. besides that, Pancasila is also a way of life for the Indonesian nation. With the rapid development of technology, the acceleration of globalization is the same. This article will describe the implementation of Pancasila values ​​that must be applied so that the values ​​of Pancasila remain strong, it is necessary to strengthen the values ​​of Pancasila to the next generation of the nation, especially for students from elementary school to tertiary level. This can be pursued by learning about citizenship and also Pancasila. This article was created to keep Pancasila as a guideline in everyday life so as to make people who believe and fear one God, have a noble character, are independent, are democratically responsible, and become citizens who uphold the values ​​of Pancasila. This article is made with a qualitative method of collecting data through literature review with sources from various data, which contain studies on the implementation of Pancasila values ​​in the era of globalization, such as in books, articles and journals.